Health Anxiety in Panic Disorder, Somatization Disorder and Hypochondriasis - Özgün Karaer KARAPIÇAK; Selçuk ASLAN; Çisem UTKU (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Health anxiety is the fear of being or getting seriously sick due to the misinterpretation of physical symptoms. Severe health anxiety is also named as hypochondriasis. Belief of having a disease due to the misinterpretation of physical symptoms is also seen in panic disorder and somatization disorder. The aim of this study is to search the health anxiety in panic disorder, somatization disorder and hypochondriasis and compare it with healthy volunteers. Method: SCID-I was used to determine psychiatric disorders in patient group. In order to assess the clinical state and disease severity of the patient group; Panic and Agoraphobia Scale, Hamilton Anxiety Rating Scale, Inventory of Depressive Symptomatology were used for patients with panic disorder and Symptom Interpretation Questionnaire, Hamilton Anxiety Rating Scale, Inventory of Depressive Symptomatology were used for patients with somatization disorder and hypochondriasis. Brief Symptom Inventory was used to assess psychopathology in healthy group. In order to evaluate health anxiety of both groups, Health Anxiety Inventory-Short Form was used. Results: Results of this study support that health anxiety is a significant major component of hypochondriasis. On the other hand, health anxiety seems to be common in panic disorder and somatization disorder. Health anxiety also may be a part of depression or present in healthy people. Conclusion: Further studies are needed in order to search how to manage health anxiety appropriately and which psychotherapeutic interventions are more effective.